FRACTION LEARNING USING DAILY CONTEXT FOR PRE-SERVICE PRIMARY SCHOOL TEACHER EDUCATION - Lisnani Lisnani (Jupitek)
Fractions are important material to understand because fractions are often encountered in everyday life. This research aims to analyze the fraction learning process using the PMRI approach for pre-service primary school teachers. This type of research is descriptive qualitative research with a PMRI approach using the context of everyday life. The subjects of this research were 20 students at second semester. Data collection techniques included tests, documentation and observation. The data analysis technique uses the Miles and Huberman model. The results of this research are a description of the thinking framework of pre-service primary school teachers using daily life contexts in the form of objects and food in determining the concept of fractions. Students are able to implement the concept of fractions using the   PMRI approach through the use of the context of objects and food that exist in everyday life. It is that this research will become a guide in learning fractions and can be developed into student worksheets